The genus Aeolothrips in Iran (Thysanoptera: Aeolothripidae) with one new species - Minaei, Kambiz (Zootaxa, 2013)
Aeolothrips zurstrasseni sp. n. is described from Fars Province, and A. modestus zur Strassen is newly recorded from Iran, in Isfahan Province. Both species have been collected from the flowers of Suaeda sp. (Chenopodiaceae), and the presence of several species of thrips on plants of this family is discussed. Recent records of Aeolothrips balati and A. citricinctus fromIran are not accepted here.